OP83 How much of the effect of disability acquisition on mental health is mediated through employment and income? A causal mediation analysis quantifying interventional indirect effects using longitudinal data from working age australians. (3rd September 2019) - Aitken, Z; Simpson, JA; Bentley, R; Blakely, T; Kavanagh, AM
Abstract : Background: There is evidence that disability acquisition causes a decline in mental health, but few studies have examined the causal mechanisms through which the effect operates. Our previous research examined three broad groups of socioeconomic characteristics and found that material factors, rather than psychosocial or behavioural, predominately mediated the effect. However, there remains a lack of understanding about which specific material factors drive the association, limiting the development of effective interventions to improve the mental health of people with disabilities. This study examined how much changes to employment and income mediate the effect of disability acquisition on mental health. Methods: We used data from the Household, Income and Labour Dynamics in Australia Survey, a longitudinal study of Australian households, which collects information annually on a wide range of demographic, social, economic, and health characteristics. We used four waves of data (2011–2014) to compare self-reported mental health between working aged individuals who acquired a disability (n=233) and those who remained disability-free (n=5419). Mental health was measured using the mental health inventory, a subscale of the SF-36 health questionnaire. We conducted a causal mediation analysis to quantify interventional indirect effects of disability acquisition on mental health operating through two distinct mediators: employment status and household income. This novel method enables quantification of path-specific effects operating through multiple mediators. We used multiple imputation with 50 imputed datasets to account for missing data and conducted analyses in Stata/SE 15. Results: Disability acquisition was estimated to cause a five-point decline in mental health (estimated mean difference: −4.8, 95% CI −7.0, −2.7). The interventional indirect effect through employment was estimated to be a 0.5 point difference (−0.5, 95% CI −1.0, 0.0), accounting for 11% of the total effect, whereas there was no evidence that income explained any of the effect. Conclusion: Using a novel approach to mediation analysis which addresses limitations of traditional mediation methods and can be estimated under weaker assumptions than natural indirect effects, we found that some of the effect of disability acquisition on mental health was explained by changes to employment, but not income. Key limitations included strong assumptions about unmeasured confounding and the small number of people acquiring a disability in our dataset. The findings have important policy implications, highlighting the need to improve employment opportunities and vocational training for people who acquire a disability to improve mental health and reduce current mental health inequalities experienced by people with disabilities.